CONTRAST-ENHANCED MAMMOGRAPHY AS THE NEW STANDARD IN BREAST HEALTH CARE - Stevanović, Kristina; Maričić, Bojana; Radovanović, Jovana (HEALTH CARE, 2024)
Contrast-enhanced mammography (CEM) has become a ubiquitous method in breast diagnostics over the last few decades, especially in recent years. There is an increasing body of strong evidence regarding the high diagnostic efficiency and sensitivity of CEM in detecting breast cancer. There is more and more evidence about the high diagnostic effectiveness and sensitivity of CEM in detecting breast cancer. Also, new research has shown similarity in the efficiency and sensitivity of CEM compared to magnetic resonance, with fewer cases of false positive results. As the application of CEM expands from potential use in screening for women with dense breast tissue to the staging of known breast malignancy, it becomes increasingly important to become well-versed in this method and its implementation. This review article will perceive the importance of CEM both for screening and in the diagnostic procedure, with a special emphasis placed on the advantages and disadvantages compared to ultrasound, standard mammography and MRI.